Equipe Maker Steam: uma metodologia ativa para uma aprendizagem criativa - CORDOVIL, Kleverton Robson da Silva (Universidade Federal do Pará, 2023)
The territory of this research involves creative learning in order to answer the following question: How can a methodology with an emphasis on team collaboration contribute to creative learning in higher education? The overall goal is to investigate and experiment with the potential of an active methodology, inspired by the STEAM movement and Maker Culture, with an emphasis on team collaboration and engagement, to promote creative learning in higher education. As a research method, we adopted the cartography method, which allows the researcher to transit and be part of the possible territories of the research, since it is a research-intervention that seeks to map subjective processes in order to make visible what happens in encounters, crossings and experiences. The method transforms a goal-determined walk (hódos) into a hódos-metá, a walk that is created and transformed during the research. It is a rhizomatic movement, focused on experience and the use of clues. Here, the clues chosen were: i) research-intervention; ii) cartographer's attention; iii) following processes; and iv) narrative politics. As narrative we were inspired by the book "The War of the Worlds" by Herbert George Wells. This work presents the hostile arrival of aliens on planet Earth, which facilitates the adaptation of some real facts that occurred between the years 2021 and 2022. The theoretical foundations that guide the concept of creative learning adopted in this research appropriates the contributions of Paulo Freire (1996, 2014) on learning, the main ideas of psychoanalyst Donald Winnicott (1975) on creativity, the contributions of artist Ostrower (2014) on sensitivity and creativity, the thought of pedagogue Jorge Larrosa (2014) on experience, and the contributions of researcher Ivani Fazenda (2008) on interdisciplinarity. Concept that intertwines with learning with the other to strengthen the individual's perception of collectivity and increase their confidence, which makes learning participatory and autonomous. In this context, the STEAM movement allied with the Maker culture presents itself as an interdisciplinary proposal, capable of integrating theory and practice, with the perspective of originating knowledge through experience. To produce the research data, workshops were held with higher education students and the cartographies carried out mapped the creative and innovative potential of the Maker Steam Team. As a consequence of the encounters and crossings that took place during the research, a methodology guide was created.